Simulations of bubble growth and interaction in high viscous fluids using the lattice Boltzmann method - Cubeddu, Alessandro; Rauh, C.; Ulrich, V. (International Journal of Multiphase Flow, 2017)
Phenomena of growth, coalescence and breakdown of bubbles within high viscous fluids are of great interest in the fluid dynamics of multiphase fluids because of their industrial relevance, e.g. in polymer, metal alloy and food processing fields. The dynamics of multiple bubble growth in hot viscous fluids is a complex issue governed by pressure forces, vapour diffusion, surface tension and viscous forces. Effects of water evaporation from the mixture surface are responsible for phenomena like glass transition, viscous increase and dough solidification. This article presents Lattice Boltzmann simulations of nucleating bubbles with large density ratio, that grow and interact in a hot high-viscous fluid. The work focuses on the first phases of the bubble expansion, neglecting the effects of evaporation. The simulations are performed using the Lattice Boltzmann Method (LBM). The Free Surface method is used to reduce a liquid/gas two-phase flow to a single-phase flow. The interface layer between gas and fluid is tracked using the volume of fluid (VOF) method. To avoid numerical instabilities due to the high viscosity (n = 100 Pa s), the problem is scaled from physical to LB-units through non-dimensional quantities. The bubbles are initially punched randomly into the domain with a dimension comparable with the dimension of nucleation and are allowed to grow under an internal over-pressure. The simulated final structure of the bubbles is compared with images of a pure starch fluid, extruded under same conditions. It is shown as the final bubble distribution, matrix dimension and bubble diameters in the simulation are in good agreement with the real final conformation.
EAM Import::2019-03-13